THE IMPACT OF CSR INCIDENTS ON CUSTOMER LOYALTY: A COMPARATIVE ANALYSIS OF INDITEX IN THE NETHERLANDS AND INDONESIA - Zaafira Ramadhani, Nashita (PEOPLE: International Journal of Social Sciences, 2024)
This study explores the relationship between corporate social responsibility (CSR) incidents and customer loyalty, focusing on a comparative analysis of Inditex’s operations in the Netherlands and Indonesia. Investigating the impact of CSR incidents on customer loyalty is crucial in understanding consumer behavior in diverse cultural contexts. Through a comprehensive examination of Inditex’s CSR practices and incidents, this study aims to discern the varying degrees of influence on customer loyalty in these two distinct markets. This research considers the moderating effect of the customer country of residence between Indonesia and the Netherlands and the relationship between CSR incidents and customer loyalty is mediated by the trust in the company’s reputation. This research contributes to the broader understanding of the global implications of CSR strategies on customer relations, offering practical implications for businesses navigating diverse markets.